Glucokinase activation repairs defective bioenergetics of islets of Langerhans isolated from type 2 diabetics - Doliba, Nicolai M. (American Physiological Society, 2012)
It was reported previously that isolated human islets from individuals with type 2 diabetes mellitus (T2DM) show reduced glucose-stimulated insulin release. To assess the possibility that impaired bioenergetics may contribute to this defect, glucose-stimulated respiration (V̇o(2)), glucose usage and oxidation, intracellular Ca(2+), and insulin secretion (IS) were measured in pancreatic islets isolated from three healthy and three type 2 diabetic organ donors. Isolated mouse and rat islets were studied for comparison. Islets were exposed to a “staircase” glucose stimulus, whereas IR and V̇o(2) were measured. V̇o(2) of human islets from normals and diabetics increased sigmoidally from equal baselines of 0.25 nmol/100 islets/min as a function of glucose concentration. Maximal V̇o(2) of normal islets at 24 mM glucose was 0.40 ± 0.02 nmol·min(−1)·100 islets(−1), and the glucose S(0.5) was 4.39 ± 0.10 mM. The glucose stimulation of respiration of islets from diabetics was lower, V(max) of 0.32 ± 0.01 nmol·min(−1)·100 islets(−1), and the S(0.5) shifted to 5.43 ± 0.13 mM. Glucose-stimulated IS and the rise of intracellular Ca(2+) were also reduced in diabetic islets. A clinically effective glucokinase activator normalized the defective V̇o(2), IR, and free calcium responses during glucose stimulation in islets from type 2 diabetics. The body of data shows that there is a clear relationship between the pancreatic islet energy (ATP) production rate and IS. This relationship was similar for normal human, mouse, and rat islets and the data for all species fitted a single sigmoidal curve. The shared threshold rate for IS was ∼13 pmol·min(−1)·islet(−1). Exendin-4, a GLP-1 analog, shifted the ATP production-IS curve to the left and greatly potentiated IS with an ATP production rate threshold of ∼10 pmol·min(−1)·islet(−1). Our data suggest that impaired β-cell bioenergetics resulting in greatly reduced ATP production is critical in the molecular pathogenesis of type 2 diabetes mellitus.